2013
DOI: 10.3382/ps.2013-03142
|View full text |Cite
|
Sign up to set email alerts
|

SavorPhos as an all-natural phosphate replacer in water- and oil-based marinades for rotisserie birds and boneless-skinless breast

Abstract: As consumer demand for all-natural marinades increases, the need to replace phosphate with a natural product that can produce equivalent or improved yield in products such as but not limited to rotisserie chickens (whole birds without giblets) and boneless/skinless breast (BSB) is a challenge for processors. The objective of this study was to determine if using an all-natural nonphosphate blend (SavorPhos-200, SP) in water-based (WB) and oil-based (OB) marinades would perform better than a commercial phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…However, in the present study, treatment 4 had higher moisture contents and lower cooking loss. Thus, the increased tenderness of these samples may be attributed to the lower cooking loss, as was found by Casco et al (2013) . However, springiness and cohesiveness were enhanced with increasing amount of added egg shell calcium in the present study.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, in the present study, treatment 4 had higher moisture contents and lower cooking loss. Thus, the increased tenderness of these samples may be attributed to the lower cooking loss, as was found by Casco et al (2013) . However, springiness and cohesiveness were enhanced with increasing amount of added egg shell calcium in the present study.…”
Section: Resultsmentioning
confidence: 54%
“…However, samples with egg shell calcium (treatments 2, 3, or 4) had lower CIE L* values ( p < 0.05) than the negative control (−), the positive control (+), or treatment 1, and the CIE L* values decreased as the addition ratio of egg shell calcium increased. pH values are related to color (lightness) of cooked meat products, as the higher the pH value, the darker the color ( Barbut, 2009 ; Casco et al , 2013 ; Sams and Alvarado, 2004 ). In the current study, products formulated with natural calcium powders (treatments 1, 2, 3, and 4) were redder (higher CIE a* values; p <0.05) than the positive control (+) and the highest CIE a* values were observed ( p <0.05) in treatment 4 (0.5% egg shell calcium added).…”
Section: Resultsmentioning
confidence: 99%
“…Ingredients like starches, proteins, fibres, hydrocolloids and bicarbonate salts can also improve WHC and cook yield when used in meat products (Petracci et al, 2013). Many studies have been made on these ingredients to improve the WHC of meat products without any added phosphates (Resconi, Keenan, Garcia, et al 2016b;Prabhu & Husak, 2014;Casco et al, 2013;Sousa et al, 2017). For example, the study of Wachirasiri et al (2016) investigated the phosphate replacing ability of sodium bicarbonate at low concentration for freezing of white shrimp (Penaeus vannamei).…”
Section: Water-binding and Emulsifying Propertiesmentioning
confidence: 99%
“…It was concluded that the shrimps treated with NaHCO 3 /lysine each at 1% (w/v) improved the water holding capacity and cooking yield (100.45%, w/w) similar to that of STPP treated samples (101.73%, w/w), proving that NaHCO 3 can act as a possible phosphate replacer. In a study by Casco et al (2013), SavorPhos -mixture of citrus flour that is rich in fibre content, all-natural flavourings and less than 2% sodium carbonate is used as phosphate replacer in water and oil-based marinades in rotisserie birds and boneless-skinless breast. SavorPhos when used in water marinade resulted in equal performance in WHC and cook loss as that of control phosphate blend whereas when used in oil marinade, it increased WHC and decreased cook loss.…”
Section: Water-binding and Emulsifying Propertiesmentioning
confidence: 99%
“…Despite these multifunctional benefits, the use of phosphates has dropped in the last decade because of poor consumer perception associated with health risks (Kim et al, 2017; Petracci et al, 2013; Watanabe et al, 2016). Therefore, recent years has witnessed an increase in efforts to find phosphate substitutes from natural sources (Casco, 2013; Cho et al, 2017; Jarvis et al, 2012). Ruusunen et al (2003) investigated the physical and sensory properties of low-salt phosphate-free frankfurters prepared by using amounts of modified tapioca starch, sodium citrate, and wheat bran at different salt and fat levels.…”
Section: Introductionmentioning
confidence: 99%